CERTAIN ISSUES OF IMPROVING SPECIAL ADMINISTRATIVE COERCIVE MEASURES IN THE FORM OF THE USE OF SPECIAL MEANS BY INTERNAL AFFAIRS BODIES (E Global Congress, 2025)
This article analyzes the part of the application of special administrative coercive measures by internal affairs bodies in the form of the use of special means related to the deployment of electroshock devices. It also provides proposals and considerations for improving legal norms aimed at restricting the use of these devices under specific conditions and in certain situations.